2022
DOI: 10.21037/atm-22-5935
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-dose radiation in human papillomavirus-associated oropharyngeal carcinoma can improve outcome: a systematic review and meta-analysis

Abstract: Background: Despite its effectiveness, the standard course of chemoradiation for the treatment of human papillomavirus (HPV)-related oropharyngeal carcinoma (OPC) results in considerable treatmentrelated adverse effects. Studies proved that HPV-positive OPC is very sensitive to radiotherapy. Using deescalation therapy as a new strategy is critical to maintaining positive outcomes while alleviating side effects.However, some studies hold that reduced dose causes insufficient effect on tumor killing. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For patients with low-risk disease, the 2-year PFS of patients who did not receive postoperative treatment was favorable. Further, Yang et al [ 42 ] conducted a meta-analysis of RT reduction in HPV-associated OPSCC. The 3-year OS rate was higher in the reduced-dose group than in the standard-dose group (91.5% vs. 87.46%).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…For patients with low-risk disease, the 2-year PFS of patients who did not receive postoperative treatment was favorable. Further, Yang et al [ 42 ] conducted a meta-analysis of RT reduction in HPV-associated OPSCC. The 3-year OS rate was higher in the reduced-dose group than in the standard-dose group (91.5% vs. 87.46%).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Furthermore, no benefit to concurrent chemotherapy was observed. Yang et al similarly conducted a meta-analysis of 13 studies for patients with HPV-positive oropharyngeral cancer and concluded that the 2-and 3-year OS rates in the de-escalated radiation group (96% and 92%, respectively) were superior to those in the standard-dose group (88% and 87%, respectively) leading them to conclude that alleviates the treatment toxicities without compromising survival in this population (99).…”
Section: De-escalated Radiationmentioning
confidence: 99%